PEMBINAAN NARAPIDANA LANJUT USIA DI LP KARANGASEM - Beliferdo, Agung; Yusa Darmadi, A. A. Ngurah; Tjatrayasa, I Made (Kertha Wicara : Journal Ilmu Hukum, 2013)
A prisoner who is being throughout punisment at prison basicly during throughout of punishment has been lose of freedom to move, it mean the prisoner only conduct activity only at the prison. Form of treatment that written in the prison effort to build the prisoner, to known her/hisself so that change his/herself become better, become positive and they will not conduct criminal again and develop theirself become useful for state, religion and their family. The efforts has been got by the correctional institution to avoid criminal repetition as describe before is through build. Implementation of build for the prisoner consist of many program on the prisoner life aspect. Build program for the prisoner that given as the efforts to prevent occurance of criminal repetition.
Keywords: Correctional Institutional, Builder, Avoid of Criminal Repetition